Arms Race Model via p-Fuzzy System - Brito, Marcelo Teles da Silva; Simões, Francielle Santo Pedro (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2024)
This article presents an adaptation of the arms race model developed by Richardson, which is based on a system of differential equations, via set theory and fuzzy logic. To this end, we implemented a fuzzy inference system combined with traditional numerical methods with the aim of solving the differential equations proposed by Richardson when the field of directions is only partially known. This methodology allows the specialist to understand and modify complex mathematical models intuitively without losing mathematical rigor.